2008
DOI: 10.1007/s10439-008-9462-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mechanical Loading on the Metabolism of Growth Plate Chondrocytes

Abstract: It is well known that mechanical loading influences the endochondral bone formation essential for the growth and development of longitudinal bones. The question was, however, asked whether the effect of mechanical loading on the chondrocyte metabolism is dependent on the loading frequency. This study was aimed at evaluating the effect of tensile loadings with various frequencies on the proliferation of growth plate chondrocytes and extracellular matrix synthesis. The chondrocytes obtained from rib growth plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 64 publications
(68 reference statements)
1
51
0
Order By: Relevance
“…tensile strain, was reported to enhance proliferation within the growth plate [13]. This, however, has been shown to be dependent on the loading frequency [7]. In our experiments we exposed CPCs from the human growth plate to a relatively low loading frequency of 0.1 Hz and a surface elongation of 3 %.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…tensile strain, was reported to enhance proliferation within the growth plate [13]. This, however, has been shown to be dependent on the loading frequency [7]. In our experiments we exposed CPCs from the human growth plate to a relatively low loading frequency of 0.1 Hz and a surface elongation of 3 %.…”
Section: Discussionmentioning
confidence: 93%
“…Pro-inflammatory cytokines stimulate the remodelling of the extracellular matrix and cell differentiation towards both osteogenic and chondrogenic lineages [5,6]. Mechanical stimuli influence growth plate chondrocyte metabolism, dependent on loading type and frequency [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ueki et al (Ueki et al, 2008) showed that mechanical loading of the growth plate of Wistar rats resulted in increased chondrocyte proliferation and matrix formation. For the current study, this suggests that elevated mechanical loading could result in lower scaled cell counts for the reserve and hypertrophic zones and higher counts for the proliferative zone, as the loading regimen increases the rate at which reserve zone cells enter the proliferative phase and hypertrophic cells become incorporated into the bony matrix of the limb element.…”
Section: Controlling For Cohortmentioning
confidence: 99%
“…The rate of matrix synthesis decreases as the static hydrostatic pressure increases up to 50 MPa [46,179]. In contrast, cyclic loading can stimulate matrix synthesis [165,174]. However, physiologic responses to cyclic loading have been shown to be temporally-and spatially-dependent since extracellular osmolality is not homogeneous across the depth of each cartilage layer [46,50,165,167,178,180].…”
Section: Mechanotransduction Processes In Articularmentioning
confidence: 99%
“…Under mechanical loading, chondrocytic proliferation and differentiation [46,165] result in a greater number of cells for the synthesis of extracellular matrix (ECM) components (collagen, proteoglycans). For example, intermittent tensile stresses applied to chondrocytes from the rat rib growth plate increased both DNA and proteoglycan synthesis by about 1.5-fold [174]. Newly formed collagen is used for the maintenance and repair of damaged extracellular matrix, while providing a support medium for the proteoglycans to trap water in order to resist compression.…”
Section: Mechanotransduction Processes In Articularmentioning
confidence: 99%